Sistem Pakar Menggunakan Metode Certainty Factor dalam Menganalisis Penyakit Karies Gigi pada Manusia - Fajri Ilhami Andrean; Y Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2021)
Caries is a dental disease that is often found, which is a disease of the hard tissues of the teeth in the form of continuous loss of mineral ions on the surface of tooth enamel, which is mostly caused by bacterial metabolism. A low level of awareness in caring for teeth causes a bad impact on dental health and on body health. At present time, people generally do not have knowledge of analyzing dental caries disease, which can later cause severe damage to teeth, such as the death of the dental pulp. This study aims to analyze caries disease using the Certainty Factor method. In this study, 50 data sets were processed, obtained from interviews with experts at the Rahmatan Lil Alamin Clinic, Padang, Indonesia. They found several factors that cause dental caries disease in humans. The data was obtained from the medical records of patients who had undergone an examination at the clinic. The data is used to analyze the type of caries disease based on the guidance of the expert. The processing steps carried out are solving the rule, determining the weight value of each symptom and calculating the Certainty Factor value. The results obtained after testing this method show that there are 94% of people who suffer from caries disease, the type most often suffered by patients with superficial caries. The test results can analyze caries disease specifically, thus the expert system used can be recommended to help dentists analyze dental caries disease in humans